Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/13683500.2014.964190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Taiwan open policy on Chinese tourist satisfaction

Abstract: The Taiwan government has imposed a daily visitation quota with strict regulations on Chinese visitor travel modes, length of stay, and visa authorizations since July 2008. This highly controlled scheme was an attempt to maintain service quality on top of security and political considerations. The purpose of this study is to provide in-depth analysis regarding the Chinese tourist satisfaction over time under different travel modes. The results indicated that package tour (PT) visitors generally gave higher sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the past decade, tourist satisfaction has been widely recognized as one of the most influential outcome variables that affect future behaviors in tourism research, thereby attracting considerable attention from destination marketers, who gather information on tourists' appraisals of consumption experiences [61][62][63][64]. Despite the importance of satisfaction, no single accepted definition of it exists in the tourism literature [8,65].…”
Section: Tourist Satisfactionmentioning
confidence: 99%
“…In the past decade, tourist satisfaction has been widely recognized as one of the most influential outcome variables that affect future behaviors in tourism research, thereby attracting considerable attention from destination marketers, who gather information on tourists' appraisals of consumption experiences [61][62][63][64]. Despite the importance of satisfaction, no single accepted definition of it exists in the tourism literature [8,65].…”
Section: Tourist Satisfactionmentioning
confidence: 99%
“…Although extensive econometric techniques have been developed for the analysis of pooled cross sectional data (Wooldridge, 2012), in tourism market segmentation the cluster analysis is usually performed on the pooled dataset losing the information on the evolution of the phenomenon (see for instance Ferrer-Rosell & Coenders, 2018). Another common approach adopted in tourism literature, is to compare directly clusters over time, even if samples made by different units are used (see for instance Cang et al, 2017). However, as stated at the beginning of this section, comparison should be made on either harmonised or paired samples.…”
Section: Statistical Matchingmentioning
confidence: 99%
“…In the recent tourism literature, the necessity to perform accurate analyses to obtain information on temporal, spatial or cultural changes regarding a particular phenomenon has been highlighted (Cang et al, 2017;Amaro et al, 2016;Song et al, 2012Song et al, , 2011, especially in consideration of the increased multiculturalism that characterises the worldwide tourism markets (Jin et al, 2017). In this paper, a new matching-clustering procedure is suggested to obtain information on the evolution of tourists' behaviour when repeated cross-sectional data are available.…”
Section: Introductionmentioning
confidence: 99%
“…One of such basic factors is safety and security (Cang et al, 2017;Lee, Jeon, & Kim, 2011;Li et al, 2011;Pearce et al, 2013;Sparks & Pan, 2009;Wong & Lau, 2001). A study of Chinese tourists visiting the US showed that crime and safety issues were a prevalent anxiety amongst respondents, cultivating negative attitudes which contaminated evaluations of other destination attributes (Lai et al, 2013).…”
Section: Basic Factorsmentioning
confidence: 99%